Letter from Carl D. Duncan to Patricia Whiting, May 7, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
A letter from A.L. Williams of the Natural Sciences department at San Jose State College that invites Whiting to Duncan's retirement dinner.